The Emergence of Private Authority in Global Governance (Cambridge University Press, 2002)
The emergence of private authority has become increasingly a feature of the post -Cold-War world. In the Emergence of Private Authority in Global Governance, leading scholars explore the source, practices , and implications of this challenge to the authority of the state.